Young Minds Awards Nomination - Tzortzakis, Nikos G. (My University, 2026)
Young Minds Awards Nomination for “Simopoulou S, Chrysargyris A, Tzortzakis N, Petropoulos S. 2019. The use of agricultural byproducts as alternative growing media for lettuce cultivation. III International Symposium on Growing Media, Composting and Substrate Analysis. SusGro2019. 24-28 June 2019, Milan, Italy
Keywords: Sciences